The Influence of Work Discipline, Work Motivation and Work Environment on Employee Performance at the UPT Training Center for Developing Workforce Productivity at the Manpower and Transmigration Department - Bunga Nindya Navynda; Vera Firdaus; Sumartik Sumartik (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2026)
This study examines employee performance at the Workforce Productivity Development Training Center (BLP2TK) under the Department of Manpower and Transmigration of East Java Province, Indonesia. Employee performance is recognized as a critical determinant of organizational effectiveness; however, empirical evidence regarding the influence of work discipline, work motivation, and the work environment within operational public-sector institutions remains limited and inconsistent. Accordingly, this study aims to analyze the partial and simultaneous effects of work discipline, work motivation, and the work environment on employee performance. A quantitative explanatory research design was employed using a saturated sampling technique involving all 50 employees of the institution as respondents. Data were collected through structured questionnaires and analyzed using Statistical Package for the Social Sciences (SPSS) version 25, including validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²). The findings reveal that work discipline (β = 0.585; p = 0.001), work motivation (β = 0.308; p = 0.032), and the work environment (β = 0.403; p < 0.001) each exert a positive and statistically significant effect on employee performance. Simultaneously, the three variables significantly influence employee performance (F = 50.060; p < 0.001), explaining 76.6% of its variance (R² = 0.766). Among the independent variables, work motivation demonstrates the strongest contribution to enhancing employee performance. The study concludes that strengthening work discipline, fostering employee motivation, and maintaining a supportive work environment are essential managerial strategies for improving employee performance and enhancing organizational effectiveness within public-sector training institutions.